A Pilot Study - Shafique Sani Nass (SAGE Publishing, 2018)
Background: Tetanus-diphtheria vaccine (Td+) coverage has been steadily declining in Katsina State, Nigeria. The pilot study was guided by The Andersen and Newman Framework of Health Services Utilization. The goal of the pilot study was to identify the Td+ vaccination coverage and identify any association between maternal residence, educational status, occupational status, access to routine immunization services, availability of routine immunization services, perceived need for Td+, perceived severity of maternal and neonatal tetanus (MNT), and compliance with Td+ in Katsina State. Methods: A cross-sectional survey of 309 randomly selected women in Charanchi district of Katsina State, Nigeria, was conducted. Data were collected using structured questionnaire and analyzed using logistic regression model. Findings: The Td+ coverage was low at 23%. Bivariate analysis showed that age, maternal residence, educational status, availability of Td+, perception of Td+, and perception of MNT significantly affected compliance with Td+ ( P < .05, P < .05, P < .05, P < .001, P < .001, P < .001, respectively). Multiple logistic regression findings were inconclusive. Conclusion: Effective strategies to improve compliance were awareness creation on Td+ immunization schedule, risk factors associated with MNT, vaccine availability, and safety. Additionally, improving access to routine immunization services, especially in underserved communities, and effective use of Td+ coverage data were used as strategies. Implications: The pilot study suggests that the design can be used to realize more conclusive and generalizable multivariate findings in future studies.